Hubungan Pengetahuan Dan Sikap Dengan Perilaku Pemberian Asi Ekslusif Pada Ibu Yang Bekerja - Yunus, Yuliandary; Katili, Tressan Eka Putri S. (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2023)
The results of the 2018 Riskesdas showed that the exclusive breastfeeding rate for infants aged 0-6 months only reached 37.3%. The cause of not achieving exclusive breastfeeding is a need for more knowledge and understanding of lactation management, which affects maternal behaviour in exclusive breastfeeding. This study aimed to determine the relationship between knowledge and attitudes toward exclusive breastfeeding behaviour in working mothers in the Tilango Health Center working area. This type of research is a correlation study using a cross-sectional approach; the sample size used was 52 people, with a saturated sampling technique and data analysis using Spearman rank. Based on the results of the study, it was found that most respondents had sufficient knowledge with sufficient behaviour categories; the statistical test results were shown by the significance value (p = 0.000 <0.05) and the contingency coefficient (0.656). Some respondents with sufficient attitude have sufficient behaviour in exclusive breastfeeding; the statistical test results are shown with a significance value (p = 0.001 <0.05) and contingency coefficient (0.458). The study concludes a relationship between knowledge and attitudes with exclusive breastfeeding behaviour in working mothers in the Tilango Puskesmas work area. Health workers should improve special programs for exclusive breastfeeding counselling to increase exclusive breastfeeding coverage.